7Li and 14N NMR studies of phase II–III transition in LiNH4SO4 single crystals. (December 2016) - Lim, Ae Ran
Abstract: The NMR spectra of 7 Li and 14 N nuclei in LiNH4 SO4 crystals were obtained near the phase transition temperature TC2 =284.5 K. Below TC2, the two physically inequivalent Li groups in phase III were distinguished in 7 Li NMR spectra. Meanwhile, the 14 N NMR spectra in phase II above TC2 showed four pairs of lines, where as those in phase III showed eight pairs. These changes in the resonance frequencies near TC2 were attributed to the structural phase transition. The 7 Li and 14 N nuclei in the structure are coordinated through the Li–O–H–N skeleton. Therefore, changes in their NMR spectra with temperature are correlated. The displacements of 7 Li and 14 N in LiNH4 SO4 crystals play important roles in the phase transition near TC2 . Highlights: Change in the structural geometry. two physically inequivalent Li and N groups. 14 N NMR spectra.